2014
DOI: 10.1111/oik.01604
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in echolocation vocalizations of the Himalayan leaf‐nosed bat: contribution of morphological variation and cultural drift

Abstract: Ecologists and evolutionary biologists have a long-standing interest in the patterns and causes of geographical variation in animals ' acoustic signals. Nonetheless, the processes driving acoustic divergence are still poorly understood. Here, we studied the geographical variation in echolocation vocalizations (commonly referred to as echolocation ' pulses ' given their short duration and relatively stereotypic nature, and to contrast them from the communicative vocalizations or ' calls ' ) of a widespread bat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 52 publications
(87 reference statements)
0
35
1
Order By: Relevance
“…In contrast to what has been found in birds, where genetic discontinuities are due to dialect 351 boundaries (Slabbekoorn and Smith 2002), acoustic divergence within bat species is unlikely to be small morphological differences in the vocal apparatus, or even in body size, could also be 358 responsible for producing different frequencies (Lin et al 2014). For instance, it has been shown 359 that a larger larynx produces lower frequencies than a smaller one (Jones 1999).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…In contrast to what has been found in birds, where genetic discontinuities are due to dialect 351 boundaries (Slabbekoorn and Smith 2002), acoustic divergence within bat species is unlikely to be small morphological differences in the vocal apparatus, or even in body size, could also be 358 responsible for producing different frequencies (Lin et al 2014). For instance, it has been shown 359 that a larger larynx produces lower frequencies than a smaller one (Jones 1999).…”
mentioning
confidence: 72%
“…However, it is still unclear whether it is the 50 cause or the consequence of a reduction in levels of gene flow within the species (Jiang et al 51 2013). Although it has been shown that at different geographical scales this sensory divergence 52 may emerge as a result of either direct ecological selection, genetic drift, cultural drift or indirect 53 ecological selection , Keighley et al 2017, Lin et al 2014, our understanding of 54 it is still far from complete ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results support greater roles for both acoustic adaptation and cultural isolation on acoustic divergence than neutral genetic divergence in both sexes. Acoustic patterns were correlated with genetic distance, but acoustic changes appeared to occur independently of genetic changes, suggesting that cultural drift and cultural selection have a stronger influence on the evolution of acoustic signals than neutral genetic divergence (Wright et al ., ; Byers et al ., ; Lin et al ., ; Potvin & Clegg, ). With respect to the acoustic adaptation hypothesis, ambient noise differences rather than habitat differences between populations had a greater effect on acoustic divergence.…”
Section: Discussionmentioning
confidence: 99%
“…Second, geographic variations in call characters are largely related to geographic factors such as distance between capture locations (geographic distance), latitude, and/or longitude (Chen et al., ; Jang et al., ; Lin et al., ; Sun et al., ; Yoshino et al., ). The cultural drift hypothesis predicts a positive correlation between acoustic and geographic distance because learned vocal signals between populations may have diverged stochastically via cultural transmission or social learning and copying errors.…”
Section: Discussionmentioning
confidence: 99%